Pattern and Predictive Factors of Metastasis in Lymph Nodes Posterior to the Right Recurrent Laryngeal Nerve in Papillary Thyroid Carcinoma - Zhou, Mengqian; Duan, Yuansheng; Ye, Beibei; Wang, Yuxuan; Li, Hong; Wu, Yue; Chen, Peng; Zhu, Jiajia; Jing, Chao; Wu, Yansheng; Wang, Xudong (Frontiers in Endocrinology, 2022)
Objective: The right cervical central lymph nodes include lymph nodes anterior to the right recurrent laryngeal nerve (LN-arRLN) and lymph nodes posterior to the right recurrent laryngeal nerve (LN-prRLN), and are separated by the right recurrent laryngeal nerve (RLN). LN-prRLN is a common site of nodal recurrence after the resection of papillary thyroid carcinoma (PTC). However, the complexity in anatomical structure brings difficulties in determining the surgical scope, so it is necessary to assess the pattern and predictive factors of right cervical central lymph nodes, especially LN-prRLN metastasis in papillary thyroid carcinoma. Methods: A total of 562 diagnosed PTC patients who underwent right or total thyroidectomy were enrolled in this retrospective study. The clinicopathological features were collected, univariate and multivariate analyses were performed to determine predictive factors of the right central lymph node metastasis. Results: In this study, the metastatic rates of the right CLN, the LN-arRLN and the LN-prRLN were 59.6% (335/562), 51.8% (291/562) and 30.4% (171/562), respectively. And 22.6% (127/562) of patients had both LN-arRLN and LN-prRLN metastasis. Among patients without LN-arRLN metastasis, the rate of LN-prRLN metastasis was 16.2% (44/271), accounting for 25.7% of the LN-prRLN metastasis group. Factors associated with an increased risk of LN-arRLN metastasis include male, age below 55 years, tumor size > 1cm, extrathyroidal extension (ETE), clinical lymph nodes metastasis(cN1), lateral lymph node metastasis, and left CLN metastasis. In addition, ETE, lateral lymph node metastasis, and LN-arRLN metastasis were independent factors of LN-prRLN metastasis. The predictive factors of LN-prRLN in cN0 PTC were further explored, revealing that tumor size ≥1.5cm, ETE, and LN-arRLN metastasis were independent predictors of LN-prRLN metastasis in cN0 PTC. Conclusion: The LN-prRLN should not be ignored in surgery because of its high rate of metastasis. Our findings indicate that thorough dissection of central lymph nodes, especially LN-prRLN is crucial in clinical work.